2007
DOI: 10.1108/09540910710748113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermal history on the intermetallic growth and mechanical strength of Pb‐free and Sn‐Pb BGA solder balls

Abstract: PurposeTo investigate effects of the thermal history on intermetallic thickness and morphology and on the resulting shear strength of the ball attachment for a variety of BGA components.Design/methodology/approachIn this study, a variety of BGA components with balls made of Pb‐free Sn‐Ag‐Cu (SAC) 305, Sn‐Pb eutectic and high‐temperature 90Pb‐10Sn alloys, were subjected to different thermal histories, including up to ten reflow cycles, and aged at 125°C from 24 to 336 h. The intermetallic thickness and morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Therefore, many Sn-rich alloy systems have been developed as alternative candidate Pb-free solders, which have attracted much research and trial applications in recent years (Abtew and Selvaduray, 2000;Lau et al, 2016). With a combination of process attributes (modest melting point and reasonable solderability), comparable electrical performances and good mechanical properties, the Sn-Ag-Cu system is one of the potential choices (Zhong et al, 2006;Liang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many Sn-rich alloy systems have been developed as alternative candidate Pb-free solders, which have attracted much research and trial applications in recent years (Abtew and Selvaduray, 2000;Lau et al, 2016). With a combination of process attributes (modest melting point and reasonable solderability), comparable electrical performances and good mechanical properties, the Sn-Ag-Cu system is one of the potential choices (Zhong et al, 2006;Liang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Cumulative IMC growth is a direct and known influence of thermal exposure. In a study of the relationship between the thermal history and the intermetallic microstructure for solder balls of ball-grid-array (BGA) components, Liang et al (2007a) observed continuous intermetallic layer growth and morphology changes during thermal exposure, which holds for all solder alloys (eutectic SnPb, high temperature solder 90Pb10Sn, and lead-free 96.5Sn-3.0Ag-0.5Cu), as shown in Figure 7. Multiple reflows were found to be less Source: Mattila et al (2004) detrimental in terms of IMC growth, than prolonged aging at elevated temperatures.…”
Section: Microstructure and Reliabilitymentioning
confidence: 99%
“…from the surface of the component, with a pre‐load force of 2.22 N (0.5 lb) for all tests. Precise positioning of the load probe and maintaining the preload force significantly improve the repeatability of the test results due to the effect of the BGA geometry and probe/load cell non‐linear behaviour at small loads (Liang et al , 2007; Coyle et al , 2000; BGA Ball Shear, 2000).…”
Section: Test Samples and Experimental Proceduresmentioning
confidence: 99%
“…Ball grid array (BGA) removal and replacement are required during product development, and for manufacturing and field returns. In general, a single rework on a specific location is permitted without causing excessive damage to solder joint reliability and board materials and adjacent components (Shin et al , 2001; Ho et al , 1999; Liang et al , 2007). However, BGA multiple revisions during a product development may force many engineering development boards to go through multiple removal and replacement cycles on the same BGA locations.…”
Section: Introductionmentioning
confidence: 99%